Effect of Organizational Culture, Career Development, and Job Satisfaction on the Quality of Employee Work-Life at the Airport Management Office of Mopah Class I Airport, Merauke - Jamaludin; Suratini; Mery Noviyanti (Britain International for Academic Research (BIAR-Publisher), 2024)
The study aimed to test and analyze the effect of organizational culture, career development, and job satisfaction on the quality of employee work-life at the Airport Management Office (UPBU) of Mopah Class I Airport, Merauke. The study used a quantitative research design and collected data through questionnaires distributed to all 110 employees of UPBU of Mopah Class I Airport, Merauke. The data analysis used multiple linear regression. The findings showed that organizational culture, career development, and job satisfaction had a positive and significant effect on the quality of employee work-life. These results serve as evidence of the importance of fostering a supportive organizational culture, providing career development opportunities, and ensuring job satisfaction to improve the overall quality of employee work-life.